Bioremediation of nitrogen- and phosphorus-polluted aquaculture sediment by utilizing combined immobilized effective microorganisms and - Wang, Liangkai; Shao, Xiaohou; Xu, Ming; Chen, Shuang (International Journal of Agricultural and Biological Engineering, 2019)
The endogenous release of nitrogen and phosphorus from aquaculture sediment can continuously pollute the water quality in aquaculture ponds. In this study, an integrated bioremediation approach that combined effective microorganisms (EM) with aeration techniques was designed to restore contaminated aquaculture sediment. Initially, a set of laboratory-scale experiments was designed to evaluate the feasibility of the technology for the bioremediation of nitrogen and phosphorus. The removal and transformation efficiency indexes of both the overlying water and sediment were measured. From the obtained results, the combination of sediment aeration and immobilized EM significantly improved the nitrogen and phosphorus removal rate from the overlying water and sediment when compared to other methods. Subsequently, a series of field-scale experiments was further implemented to assess the integrated technique in practical applications. In field experiments, the variation in the comprehensive trophic level index (TLI) and sediment biodegradation activities (G value) was used to assess the effect of sediment bioremediation. In pond II which promotes sediment biodegradation, the values of TLI varied from 70.13 to 54.16, and the classification level changed from Hypereutrophic to a Light eutrophic. In addition, the G value increased from 0.98 kg/(kg·h) to 2.12 kg/(kg·h). The organic matter (OM) and sediment thickness (ST) decreased by 17.4 g/kg and 2.3 cm, respectively. The obtained results indicated that the combination of EM and sediment aeration might be feasible and effective for the remediation of nitrogen- and phosphorus-polluted aquaculture sediment.Keywords: effective microorganisms, immobilization technology, aeration, aquaculture sediment, bioremediationDOI: 10.25165/j.ijabe.20191206.4904Citation: Wang L K, Shao X H, Xu M, Chen S. Bioremediation of nitrogen- and phosphorus-polluted aquaculture sediment by utilizing combined immobilized effective microorganisms and sediment aeration technology. Int J Agric & Biol Eng, 2019; 12(6): 192–201.